Muscle moves mass: Deconstructing the culture of weight loss in American Olympic Weightlifting - Nelson, M.; Jette, S. (International Review for the Sociology of Sport, 2023)
Sport scholars have argued that to protect athlete health, competitive sport cultures must begin to de-emphasize the importance of leanness for athletic performance. However, there is a notable lack of analyses of the pressures towards leanness experienced by athletes in sports that are not considered most `at-risk` for the development of disordered bodily practices, such as Olympic Weightlifting. Based on interviews with sixteen competitive American Olympic Weightlifters, this study uses Foucauldian insights about the inseparability of culture, language, and the body to examine how weightlifters come to understand—and rationalize—their weight classes, body compositions, and avoidance of body fat. We find that while weightlifters characterized a wide range of body compositions as being functional for the sport, their own weight class choices were informed by a sport-specific narrative that condemned body fat. We critically interrogate this preference for leanness-focused bodily practices in a `non-lean` sport, looking to the `Sport Ethic` and other dominant bodily discourses as possible sources of influence.